Broad-band X-ray observations of the 2018 outburst of the changing-look active galactic nucleus NGC 1566. Issue 1 (29th July 2021) - Jana, Arghajit; Kumari, Neeraj; Nandi, Prantik; Naik, Sachindra; Chatterjee, Arka; Jaisawal, Gaurava K; Hayasaki, Kimitake; Ricci, Claudio
ABSTRACT: We study the nature of the changing-look active galactic nucleus NGC 1566 during its 2018 June outburst. During the outburst, the X-ray intensity of the source rises up to ∼25–30 times compared to its quiescent state intensity. We perform timing and spectral analysis of the source during pre-outburst, outburst, and post-outburst epochs using semisimultaneous observations with the XMM–Newton,   Nuclear Spectroscopic Telescope Array ( NuSTAR ), and Neil Gehrels Swift Observatories. We calculate variance, normalized variance, and fractional rms amplitude in different energy bands to study the variability. The broad-band 0.5–70 keV spectra are fitted with phenomenological models, as well as physical models. A strong soft X-ray excess is detected in the spectra during the outburst. The soft-excess emission is found to be complex and could originate in the warm Comptonizing region in the inner accretion disc. We find that the increase in the accretion rate is responsible for the sudden rise in luminosity. This is supported by the 'q'-shape of the hardness-intensity diagram that is generally found in outbursting black hole X-ray binaries. From our analysis, we find that NGC 1566 most likely harbours a low-spinning black hole with the spin parameter a * ∼ 0.2. We also discuss a scenario where the central core of NGC 1566 could be a merging supermassive black hole.